2015
DOI: 10.1097/mca.0000000000000243
|View full text |Cite
|
Sign up to set email alerts
|

Lower AMP-activated protein kinase level is associated with the vulnerability of coronary atherosclerotic plaques by attenuating the expression of monocyte autophagy

Abstract: Therefore, our work is novel in showing that AMPK of PBMs may decrease plaque vulnerability and subsequent plaque rupture through activation of autophagy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…AMPK is an evolutionarily conserved sensor of cellular energy receptor and plays a critical role in glucose and lipid metabolism, as well as the induction of autophagy ( Kahn et al, 2005 ; Zhang et al, 2016 ). Our previous studies have shown that a lower AMPK activation level was associated with coronary atherosclerotic plaque vulnerability by attenuating autophagy in peripheral blood monocytes ( Cheng et al, 2015 ). In addition, Rb1 has also been shown to be able to promote AMPK phosphorylation in rats ( Shen et al, 2013 , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…AMPK is an evolutionarily conserved sensor of cellular energy receptor and plays a critical role in glucose and lipid metabolism, as well as the induction of autophagy ( Kahn et al, 2005 ; Zhang et al, 2016 ). Our previous studies have shown that a lower AMPK activation level was associated with coronary atherosclerotic plaque vulnerability by attenuating autophagy in peripheral blood monocytes ( Cheng et al, 2015 ). In addition, Rb1 has also been shown to be able to promote AMPK phosphorylation in rats ( Shen et al, 2013 , 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of AMPKα is diminished during atherogenesis, which leads to decreased autophagy and paradoxical upregulation of SREBP-1c and SREBP-2, as well as further progression of atherosclerosis 79, 80 . Restoring AMPKα expression protects from atherogenesis 81, 82 .…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore widely employed in surgical anesthesia and operations of diagnosis and treatment, such as minor surgery, gastrointestinal endoscopy and interventional therapy (4). Animal studies have demonstrated that isoflurane and inhalation anesthetics induce apoptosis of neurocytes in neonatal animals and further damage cognitive function (3).…”
Section: Introductionmentioning
confidence: 99%